Autonomy of English language learners: A scoping review of research and practice - Chong, Sin Wang; Reinders, Hayo (Language teaching research : LTR, 2025)
Learner autonomy is a vibrant and diverse field. In its approximately 40-year history, it has drawn liberally on theoretical constructs and research methodologies from other disciplines. In turn, it has contributed to the field of applied linguistics by drawing attention to the fundamental importance of understanding the language learner as an active agent in the learning process. To understand the role of autonomy in, and its connections with other areas of study, it is important to ask how it has been conceptualized and operationalized. In addition, given its elusive and amorphous nature, it is timely to ask if and how (the development of) learner autonomy has been evaluated. In this article we conducted a scoping review, or a systematic and comprehensive literature review, of 61 empirical studies in this field. The results show a rich array of conceptualizations and numerous operationalizations, in addition to a somewhat limited use of evaluations. We draw from this a number of implications for research. In particular, we encourage learner autonomy researchers to make explicit their theoretical frameworks, extend their investigation to the role of language learning beyond the classroom in promoting learner autonomy, and diversify their use of research methods.